The influence of organisational justice on Perceived Organisational Support in a university recreational sports setting. (26th June 2009) - Jordan, Jeremy S.; Turner, Brian A.; Pack, Simon M.
Using a sample of 152 student employees, the authors examined the relationship between organisational justice and Perceived Organisational Support (POS). Specifically this study examined the degree that distributive, procedural, and interactional justice influenced student employee POS. Additionally, the authors explored whether perceptions of justice differed based on sex, tenure of employment, and type of supervision. All three dimensions of organisational justice were significantly related to POS, with distributive justice demonstrating the greatest effect. Based on findings from this study, it appears that employee perceptions of workplace fairness serve as an important determinant of POS.